2021
DOI: 10.1039/d0cp04308g
|View full text |Cite
|
Sign up to set email alerts
|

On the adsorption mechanism of caffeine on MAPbI3 perovskite surfaces: a combined UMC-DFT study

Abstract: Recently, it was experimentally shown that the performance and thermal stability of the perovskite MAPbI3 were improved upon the adsorption of a molecular layer of caffeine. In this work, we...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Bpy and Tpy tend to adsorb on MAPbI 3 in a tilted orientation, which is similar to other π-conjugated PMs. [59][60][61] As expected, the adsorption configurations with the N atoms of Bpy/Tpy in the same direction have an advantage over those with the N atoms in the inverse direction which are unable to match well with the Pb of MAPbI 3 .…”
Section: Geometric Structure and Adsorption Energysupporting
confidence: 55%
See 2 more Smart Citations
“…Bpy and Tpy tend to adsorb on MAPbI 3 in a tilted orientation, which is similar to other π-conjugated PMs. [59][60][61] As expected, the adsorption configurations with the N atoms of Bpy/Tpy in the same direction have an advantage over those with the N atoms in the inverse direction which are unable to match well with the Pb of MAPbI 3 .…”
Section: Geometric Structure and Adsorption Energysupporting
confidence: 55%
“…Compared with Bpy, Tpy possesses one more pyridine ring; it needs to be determined whether it is due to its larger total electronegativity derived from an extra N atom. In addition, some passivated molecules with some large electronegative O or N atoms such as caffeine 59 and perylene diimide (PDI) 72 indeed introduce trap states into the band structure. To verify our hypothesis, a new molecule was designed based on Tpy, in which one of the pyridine rings was replaced by a thiophene ring, named Tpy-1S (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups reported that passivation molecules may lead to deep trap states in band gaps of perovskite, which is disastrous for passivation effects. 37,60,61 As shown in Fig. 4, LP has a negligible effect on the band structure of perovskite, and no deep trap state appears.…”
Section: Resultsmentioning
confidence: 87%
“…To provide a preferable match for the lattice of perovskite, these natural molecules tend to adsorb on the surface in a tilted orientation. 28,61,76 This diminishes the shielding effect of oxygen and water, resulting in unsustainable passivation upon stability. However, intelligently shrouded adsorption of LP occurs on perovskite, thus surpassing the inefficient adsorption of other natural molecules.…”
Section: Discussionmentioning
confidence: 99%